2020
DOI: 10.31744/einstein_journal/2020ao5236
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of senescence progression in mesenchymal cells from human umbilical cord walls measured by immunofluorescence and flow cytometry of p16 and p21

Abstract: Objective To follow the expansion of mesenchymal stem cells from umbilical cords by two classic senescence markers, p16 (INK4A) and p21 (CDKN1A), using practical, fast, and less expensive methods than the gold standard Western blotting technique, to evaluate its applicability in the laboratory. Methods Mesenchymal stem cells from umbilical cords were isolated from Wharton’s jelly and, after quality control, morphological and immunophenotypic characterization by flow cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
0
3
1
Order By: Relevance
“…Previous findings showed that P16 and P21 jointly regulate fibroblastic growth. [ 29 ] However, our results showed no correlation between P16 and P21 in either group. Further studies are required to explore the underlying mechanism.…”
Section: Discussioncontrasting
confidence: 74%
“…Previous findings showed that P16 and P21 jointly regulate fibroblastic growth. [ 29 ] However, our results showed no correlation between P16 and P21 in either group. Further studies are required to explore the underlying mechanism.…”
Section: Discussioncontrasting
confidence: 74%
“…We observed NANOG expression in both CMSCLC populations; however, there was decreased expression in terms of cell numbers in BAVD-CMSCLC. Furthermore, p16 an inhibitor of cell cycle progression most commonly associated with cell senescence including, tissue resident MSC and cardiomyocytes, was upregulated in BAVD-CMSCLC compared to CAD-CMSCLC [ 30 , 51 , 52 ]. While p16 is a robust marker of human senescence in vivo [ 40 ], the senescent phenotype can be heterogeneric and dependent on cell type and stimuli as such a deeper analysis of senescence-associated gene expression would provide insight into the signature of senescent CMSCLCs [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…These variables are particularly significant because the majority of studies use senescence-enriched cellular populations (SEP), rather than examining a population containing only SnCs (González-Gualda et al, 2021;Jeyapalan & Sedivy, 2013;Liu et al, 2019;Menegotto et al, 2017;Silva et al, 2020) (Figure 3f). To overcome this barrier, techniques designed to isolate SnCs are essential, like cell sorting, scRNA-seq, tissue microdissection, or immunocytochemistry (Bertolo et al, 2020;Gruber et al, 2010;Magkouta et al, 2023;Wallis et al, 2022;Wang et al, 2016).…”
Section: Current Challeng E Smentioning
confidence: 99%
“…Furthermore, different cell types or subpopulations of SnCs can contribute to average levels of senescence markers in a population (Jeyapalan & Sedivy, 2013 ; Sturmlechner et al., 2022 ; Troiani et al., 2022 ), as well as non‐SnCs can also contribute with features attributed to SnCs (Gorgoulis et al., 2019 ), which is especially important in studies using primary cells from human or animal samples (Bahar et al., 2006 ; Delfarah et al., 2021 ; Tuttle et al., 2021 ). These variables are particularly significant because the majority of studies use senescence‐enriched cellular populations (SEP), rather than examining a population containing only SnCs (González‐Gualda et al., 2021 ; Jeyapalan & Sedivy, 2013 ; Liu et al., 2019 ; Menegotto et al., 2017 ; Silva et al., 2020 ) (Figure 3f ). To overcome this barrier, techniques designed to isolate SnCs are essential, like cell sorting, scRNA‐seq, tissue microdissection, or immunocytochemistry (Bertolo et al., 2020 ; Gruber et al., 2010 ; Magkouta et al., 2023 ; Wallis et al., 2022 ; Wang et al., 2016 ).…”
Section: Current Challengesmentioning
confidence: 99%